C in a nutshell the definitive reference - Prinz, Peter; Crawford, Tony (In a Nutshell, 2015)
The new edition of this classic O'Reilly reference provides clear, detailed explanations of every feature in the C language and runtime library, including multithreading, type-generic macros, and library functions that are new in the 2011 C standard (C11). If you want to understand the effects of an unfamiliar function, and how the standard library requires it to behave, you'll find it here, along with a typical example. Ideal for experienced C and C++ programmers, this book also includes popular tools in the GNU software collection. You'll learn how to build C programs with GNU Make, compile executable programs from C source code, and test and debug your programs with the GNU debugger.